A study of lattice elasticity from low entropy metals to medium and high entropy alloys. (May 2015) - Huang, E-Wen; Yu, Dunji; Yeh, Jien-Wei; Lee, Chi; An, Ke; Tu, Shan-Yi
Abstract : An equal-molar CoCrFeMnNi, face-centered-cubic high-entropy alloy system and a face-centered-cubic stainless steel described as a medium-entropy system, are measured by in situ neutron-diffraction experiments subjected to continuous tension at room and several elevated temperatures, respectively. With spallation neutron, the evolution of multiple diffraction peaks is collected simultaneously for lattice-elasticity study. Temperature variation of elastic stiffness of a single face-centered-cubic-phase Ni and a single face-centered-cubic-phase Fe are compared as low-entropy metals. The CoCrFeMnNi high-entropy alloy shows distinct lattice anisotropy.